Pump-probe spectroscopy on cubic III-nitride structures - Whale, Joshua J. (2019)
This thesis presents a series of studies applying the picosecond acoustics technique to investigate the ultrafast phonon dynamics in cubic III-nitride epilayers grown by molecular beam epitaxy on GaAs (001) substrates. The aim of these studies was twofold, firstly for the investigation and characterisation of the photo-elastic properties of zinc-blende (cubic) nitride materials. And secondly for the study of high frequency coherent phonons in sub-film-thick cubic AlGaN structures with the general aim of modulating light in the UV spectrum at up to terahertz frequencies.